Analisis Wacana Kritis dalam Bidang Pendidikan: Analisis Bibliometrik - Yusep Ahmadi F; Yusuf Anbar Firdausi; Wawan Gunawan (Ranah: Jurnal Kajian Bahasa, 2024)
This research aims to present trends and developments in the results of critical discourse analysis research in the field of education using bibliometric analysis methods. The data source for this research is AWK journal articles in the education sector indexed by Scopus. Data was collected via the Publis or Perish application, with the keywords Critical Discourse Analysis, Education and Learning; year of publication in the last 5 years, namely between 2017 s.d. 2022, Scopus indexer. Based on this technique, 52 journal articles were obtained which were declared valid according to the problem and research objectives. The research results show that the trending problem or issue studied by AWK researchers in the field of education is the issue of representation and underrepresentation of cultural values and certain cultural groups in educational discourse; the most widely used AWK model is the Fairclough AWK model; The trend for most AWK research publications in the field of education is in the journal Linguistics and Education. Meanwhile, the research country that has contributed the most to AWK research in the field of education is researchers from the United States, while the development of AWK research in the field of education indexed by Scopus in the last 5 years was mostly published in 2018. This research implies that discourse is a means of practicing social representation which is still conditional on inequality. Even though it is in the context of education, inequality still occurs. Starting from there, the recommendation for AWK researchers in the field of education is to be able to research and develop a balanced communication formula, both communication in learning resources and in the learning process. AbstrakPenelitian ini  bertujuan untuk menyajikan  tren dan perkembangan hasil penelitian  analisis wacana kritis dalam bidang pendidikan dengan metode analisis bibliometrik.  Sumber data penelitian ini adalah artikel-artikel jurnal   AWK bidang pendidikan yang terindeks Scopus. Data dijaring melalui aplikasi Publis or Perish, dengan kata kunci Critical Discourse Analysis, Education dan Learning; tahun terbit 5 tahun terakhir, yaitu antara 2017 s.d. 2022, pengindeks Scopus. Berdasarkan teknik tersebut didapatkan 52 artikel jurnal yang dinyatakan valid sesuai dengan masalah dan tujuan penelitian. Hasil penelitian menujukkan  bahwa tren masalah atau isu yang diteliti peneliti AWK dalam bidang pendidikan adalah isu representasi dan underrepresented terhadap nilai kultural dan kelompok kultural tertentu dalam sebuah wacana pendidikan; model AWK yang paling banyak digunakan adalah model AWK Fairclough; tren tempat publikasi penelitian AWK dalam bidang pendidikan yang paling banyak adalah pada jurnal Linguistics and Education. Sementara itu, negara peneliti yang paling banyak berkontribusi dalam penelitian AWK bidang pendidikan adalah peneliti asal Amerika Serikat, sedangkan perkembangan penelitian AWK bidang pendidikan yang terindeks Scopus dalam 5 tahun tahun terakhir ini banyak diterbitkan pada tahun 2018. Penelitian ini mengimplikasikan bahwa wacana merupakan sarana praktik representasi sosial yang masih syarat dengan ketimpangan. Sekalipun itu pada konteks pendidikan, ketimpangan itu masih terjadi. Berangkat dari sana, rekomendasi bagi peneliti AWK bidang pendidikan adalah untuk dapat meneliti dan mengembangkan formula komunikasi yang seimbang, baik komunikasi yang ada dalam sumber belajar maupun dalam proses pembelajaran.